Untitled
Untitled
Untitled
1.
2.
G3
G2
1 + G3 G4 H2
G1
G3
1 − G2 H1
1 + G3 G4 H2 G1 G2 G3 G4
G4 =
G3 1 + G3 G4 H2 − G2 G3 H1 + G1 G2 G3
G2
1 + G3 G4 H2
1 + G1
G3
1 − G2 H1
1 + G3 G4 H2
3. 図 2
1
1 sC
sCVo = 1
sC
1 (Vi − V0 ) = (Vi − Vo )
R2 + sC R1 + sC
(1 + sR1 C)(1 + sR2 C)
1
∴ Vo = (Vi − Vo )
(1 + sR1 C)(1 + sR2 C)
{ }
1 1
1+ Vo = Vi
(1 + sR1 C)(1 + sR2 C) (1 + sR1 C)(1 + sR2 C)
Vo 1
∴ =
Vi 1 + (1 + sR1 C)(1 + sR2 C)
図3 ( )
1 1
+ sC1 (Ei − Eo ) = 1 Eo
R1 R2 + sC
sR1 C2
(1 + sR1 C1 )(Ei − Eo ) = Eo
1 + sR2 C2
(1 + sR2 C2 )(1 + sR1 C1 )(Ei − Eo ) = sR1 C2 Eo
1
(1) 1.
[ ]
−1 10
L = 10e−5t
s+5
2.
[ ] [ ]
1 1 −1 1
L−1 = L
2s2 + 7s + 6 2 (s + 2)(s + 32 )
( )
1 3 est 1 est
= lim 3 s + 3 + lim (s + 2)
2 s→− 2 2 (s + 2)(s + 2 ) 2 s→−2 (s + 2)(s + 32 )
= e− 2 t − e−2t
3
3.
[ ] [ ]
1 1 −1 1
L−1 = L
9s2 + 12s + 4 9 (s + 23 )2
( )2
1 d 2 est 1 1
lim test = te− 3 t
2
= lim 2 s+ =
9 s→− 3 ds 3 (s + 23 )2 9 s→− 23 9
4.
[ ] [ ]
−1 24 −1 6
L =L
4s2 + 6s s(s + 32 )
( )
6 3 6
est = 4(1 − e− 2 t )
3
st
= lim s 3 e + lim 3 s + 3
s→0 s(s + )
2 s→− 2 2 s(s + 2 )
(2) 1.
10 1
y(∞) = lim s =2
s→0 s+5s
2.
1 1 1
y(∞) = lim s =
s→0 2s2 + 7s + 6 s 6
3.
1 1 1
y(∞) = lim s =
s→0 9s2 + 12s + 4 s 4
4.
24 1
y(∞) = lim s =∞
s→0 4s2 + 6s s
(3) 1.
10
y(∞) = lim s ·1=0
s→0 s+5
2.
1
y(∞) = lim s ·1=0
s→0 2s2 + 7s + 6
2
3.
1
y(∞) = lim s ·1=0
s→0 9s2 + 12s + 4
4.
24
y(∞) = lim s ·1=4
s→0 4s2 + 6s
(4) 1.
1 1 1
e(∞) = lim s 10 s = 3
s→0 1 + s+5
2.
1 1 6
e(∞) = lim s 1 =
s→0 1+ 2s2 +7s+6
s 7
3.
1 1 4
e(∞) = lim s 1 =
s→0 1+ 9s2 +12s+4
s 5
4.
1 1
e(∞) = lim s 24 =0
s→0 1+ 4s2 +6s
s